The Implementation of Environmental Sanitation in Elementary Schools: 2018 Inspection Report from Kramatwatu Sub District, Serang District, Banten Province - Devi Novianti; Wiwik Eko Pertiwi (JURNAL KESEHATAN LINGKUNGAN, 2019)
A poor sanitation conditions in School could have a negative influence on the health level of students. Moreover, it could also downgrade the quality of teaching and learning performance. This study aim to find out the overview of elementary school environmental sanitation through inspection in the North Region of Kramatwatu Sub District, in 2018. This study used a descriptive metodology. While the population of this study was total number of primary schools in Kramatwatu Sub District, Serang Regency in the North Region. The sample of this study amounted 21 elementary schools. Primary data collection was obtained from the sanitation inspection (IS) sheet, whereas the data was taken by direct observation and interviews at the research site. The results showed that 42.9% of elementary school locations, 57.1% of garden environment, 71.4% of utilization, 90.5% of the buildings, 66.7% of the floors, 19.0% of the walls, 100.0% of the roof, 85.7 % of the ceiling, 71.4% of the doors, 90.5% of the classrooms already met the standard. While, ventilation, lighting, ablution, physical quality of water, water quantity are 100% in accordance with the requirements. It was also reported 9.5% of qualified wastewater discharge, 23.8% management garbage, 0% of bathrooms and toilets have meet the requirement. Suggestions are given to make collaboration with cross-sector to improve environmental sanitation quality therefore it meets health requirements.